2015
DOI: 10.1371/journal.pone.0126481
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Air Filters Using Natural Euscaphis japonica Nanoparticles

Abstract: Controlling bioaerosols has become more important with increasing participation in indoor activities. Treatments using natural-product nanomaterials are a promising technique because of their relatively low toxicity compared to inorganic nanomaterials such as silver nanoparticles or carbon nanotubes. In this study, antimicrobial filters were fabricated from natural Euscaphis japonica nanoparticles, which were produced by nebulizing E. japonica extract. The coated filters were assessed in terms of pressure drop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 64 publications
0
34
0
Order By: Relevance
“…Several studies that have measured concentrations of bioaerosols in indoor and outdoor environments have shown that bioaerosols can significantly affect human health conditions (Ren, Jankun & Leaderer, 1999;Zhu et al, 2003). Therefore, it is necessary to monitor and control bioaerosols in the air for occupational safety and public health purposes (Hwang et al, 2015;Lee et al, 2012;Mainelis et al, 2002;Nazaroff, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies that have measured concentrations of bioaerosols in indoor and outdoor environments have shown that bioaerosols can significantly affect human health conditions (Ren, Jankun & Leaderer, 1999;Zhu et al, 2003). Therefore, it is necessary to monitor and control bioaerosols in the air for occupational safety and public health purposes (Hwang et al, 2015;Lee et al, 2012;Mainelis et al, 2002;Nazaroff, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcus epidermidis (ATCC 12228) and Micrococcus luteus (ATCC 9341) were used as the test airborne microorganisms. These Gram-positive bacteria are commonly found in indoor environments and on human skin [31,32], and are used widely in bioaerosol research [21,[33][34][35]. In particular, S. epidermidis is an important opportunistic pathogen and is the most common source of infections on indwelling medical devices [36].…”
Section: Test Particles and Microorganismsmentioning
confidence: 99%
“…In addition to its high antimicrobial activity, natural products are considered as less toxic than inorganic antimicrobial agent. Hwang et al [41] investigated the preparation antimicrobial filter by employing nebulization or aerosol process for coating a filter with Euscaphis japonica nanoparticles. They found that pressure drop and antimicrobial activities of the filter were function of deposition time.…”
Section: Antimicrobial Air Filtermentioning
confidence: 99%